Feline atopic dermatitis - KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ) A. F.; SARIDOMICHELAKIS (Μ.Ν. ΣΑΡΙΔΟΜΙΧΕΛΑΚΗΣ) M. N. (Journal of the Hellenic Veterinary Medical Society, 2018)
Atopy is a highly pruritic skin disease in cats that have positive intradermal test reactions mostly to non - seasonal allergens (house dust mites). It’s pathogenesis is unknown, though it is believed that a reaginic antibody exists resemblin IgE. Young cats appear to be predisposed. The most consistent feature of the disease is pruritus, heralding its clinical picture. The four most commonly occurring cutaneous reaction patterns are military dermatitis, eosinophilic granuloma complex lesions, selfinduced alopecia or hypotrichosis and lesionai or nonlesional pruritus of the face, neck and pinnae. The definitive diagnosis of feline atopy requires a positive intradermal allergy test reaction, good flea control, a poor response to a 9 to 13 -week course of a hypoallergenic diet and negative fungal cultures plus skin scrapings for pathogenic mites. The treatment plan may include avoidance of allergens, glucocortidoids (repositol methylprednisolon, dexamethason), ω/3 - ω/6 fatty acid supplements, antihistamines (chlopheniramine, clemastine) and/or mast cell stabilizers (oxatomide) and hyposensitization.